2020
DOI: 10.12775/jehs.2019.09.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Nursing Personnel of the Świętokrzyskie Voivodeship Hospitals on Nosocomial Infections

Abstract: Introduction: Nosocomial (also known as hospital-acquired) infections are understood as infections which develop during patient's stay in hospital, but are not the direct cause of hospitalisation. The aim of the study: The purpose of the paper was to determine the knowledge of the nursing personnel from Świętokrzyskie Voivodeship on nosocomial infections, prevention and methods of combating them. Other addressed issues included the analysis of the work yeas and education level as related to the state of nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Different studies concluded that sources of information about patients' rights as doctors, nurses, doctors-nurses, posters, media, and internet (C xelik & Tas xhan, 2014;Erer et al, 2018;E. S. Mohammed et al, 2017;Unnikrishna et al, 2017;Wrzes´niewska et al, 2017). In a different study, the importance of the role that healthcare providers such as physicians, nurses, and administrative staff have in informing patients about their rights and the exercising of patient rights and creating awareness was emphasized (P. Mohammadi, Naderiravesh, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Different studies concluded that sources of information about patients' rights as doctors, nurses, doctors-nurses, posters, media, and internet (C xelik & Tas xhan, 2014;Erer et al, 2018;E. S. Mohammed et al, 2017;Unnikrishna et al, 2017;Wrzes´niewska et al, 2017). In a different study, the importance of the role that healthcare providers such as physicians, nurses, and administrative staff have in informing patients about their rights and the exercising of patient rights and creating awareness was emphasized (P. Mohammadi, Naderiravesh, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Egypt, three quarters of the patients did not know that there was a regulation about patient rights and only 40% of the patients were aware that they deserve to be informed about their rights and responsibilities in a manner they can understand (E. S. Mohammed et al, 2017). In different studies conducted with patients, the level of knowledge and awareness of the participants about patient rights was insufficient (Abiiro et al,2020;Wrzes´niewska et al, 2017;Younis et al,2017). It is important for the patients to know and exercise their rights in their relationship with the healthcare professionals since expressing their expectation/desire from health services will contribute positively to their treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations